The Dilemma of Law Enforcement in Handling Road Blocking, Between Freedom of Expression And Road User Rights in Dompu Regency - Fitradin Malani; Ridwan; Mastorat (CV. Creative Tugu Pena, 2026)
Road blockades in Dompu Regency pose a legal dilemma because they combine two conflicting public rights: freedom of expression and the rights of road users. This action is often chosen as an effective means of public expression, but simultaneously disrupts community mobility, safety, and socio-economic activities. Field evidence demonstrates the tension between the aspirations of demonstrators and the obligation of law enforcement officials to enforce laws that protect the public interest. Regulations such as Law No. 9 of 1998, Law No. 22 of 2009, the Criminal Code, and the Police Law provide the legal basis, but their implementation faces practical obstacles. This study aims to understand how this conflict of rights is negotiated in law enforcement practices while assessing the effectiveness of existing regulations and the social and cultural factors that influence law enforcement decisions. The research approach uses normative and qualitative juridical methods, utilizing secondary legal materials and policy documents. The analysis focuses on integrating legal texts and empirical evidence to map the legal dilemma and its implications for the balance of public rights. The scope is limited to the case of road blockades in Dompu Regency to emphasize the local context and the strategies of law enforcement officials. The findings show that authorities face a dilemma between firmly enforcing the law and respecting the rights of demonstrators. Therefore, mediation, inter-agency coordination, public education, and monitoring technology are crucial strategies. Operational guidelines, risk indicators, and standard procedures are also needed to ensure proportional and consistent action by officers. The research's novelty lies in the integration of legal analysis and field facts, resulting in an adaptive and inclusive law enforcement strategy. The findings provide academic and practical contributions with recommendations for operational guidelines, community-based mediation mechanisms, increased officer capacity, and a systematic evaluation system. This strategy is expected to maintain a balance between the rights of expression and road users, prevent prolonged conflict, and strengthen legal legitimacy at the local level.